Second-Order Simple Multiphase Oscillator Using Z-Copy Controlled-Gain Voltage Differencing Current Conveyor - Sotner, R.; Jerabek, J.; Petrzela, J.; Herencsar, N.; Prokop, R.; Vrba, K. (Elektronika ir Elektrotechnika, 2014)
Interesting type of the second-order electronically controllable multiphase oscillator is introduced in this paper. Modified voltage differencing current conveyor, so-called z-copy controlled gain voltage differencing current conveyor (ZC-CG-VDCC), offers interesting features for synthesis of this type of multiphase oscillator. Available controllable parameters of the ZC-CG-VDCC (intrinsic resistance, transconductance and current gain) are fully utilized for independent adjusting of oscillation condition and oscillation frequency. Specific matching condition allows linear control of oscillation frequency that is not so typical in such simple types of oscillators. Available phase shifts are 45, 90, 135 and 180 degree. Simulation results based on CMOS model of active element confirms intentions of the proposal in the bandwidth of several MHz. DOI: http://dx.doi.org/10.5755/j01.eee.20.9.8709